Caracterización de microestructuras formadas por coloides autopropulsados y superparamagnéticos bajo un campo magnético externo: dinámica browniana y análisis de escala - De la Cruz Araujo, Ronald Abel (2018)
The microstructures formed by magnetic colloids in the absence or presence of external magnetic fields plays a key role in the design of multifunctional nanomaterials. In this work we have carried out Brownian dynamics simulations of a dilute suspension composed by self-propelled superparamagnetic colloids, in order to study the interplay between the self-propulsion and the magnetic interaction forces in their aggregation process, when the suspension is subjected to a strong external magnetic field. This simulation method solves, numerically, the force and torque balance equations which arise after applying the Newton’s second law to the translational and rotational motion of spherical magnetic particles immersed in a Newtonian fluid. The model neglects the particle inertia, the gravity effects and the hydrodynamic interparticle interactions, which is a common practice when the system is dilute and the particle sizes are in the colloidal range (size 1nm10 m). The mean cluster size and the population distributions were measured as a function of time for various combinations of Péclet number (Pe)—ratio between selfpropulsion and Brownian forces—and small dimensionless magnetic dipole-dipole strength ( 20)—ratio between the magnetic dipole-dipole and Brownian forces.It was found that as well as the Pe increases the ability of the system to aggregate increases to a critical value of Pe which depends of . After this critical Pe the average size of aggregates reach a steady state value and also depends of . At Pe ! 1 and due to the predominance of self-propulsion force with respect to the Brownian force Nc ! 1. Our analysis shows that these results are better presented as a function of the ratio Pe= , because this ratio represents the interplay between the self-propulsion force and the magnetic interaction strength. Our physical model was “validated"with the expected when Pe ! 0. These results and methodology could be used to continue exploring potential applications of recent particles synthesized with similar features (self-propelled and superparamagnetic) as used in the present model. In specific this study demonstrate that the size of chains formed by magnetic particles can be controlled changing the self-propulsion force in the system avoiding for example very long chains which can difficult their use in drug delivery, magnetic hyperthermia or other applications where very long chains is a undesired scenario.